The effect of coleus aromaticus benth extracts on the oxidative stability of palm olein / Hendrie Johann Muhamad Ridzwan ... [et al.] - Muhamad Ridzwan, Hendrie Johann; Ghazalli, Nur Fatiha; Senawi, Syamsyir Akmal; Wan Razali, Wan Aizuddin; Hamzah, Hairul Hisham; Abdul Rahman, Muhammad Nasri (2012)
This study was conducted to determine the thermal oxidative stability of palm oil in the presence of the Coleus aromaticus Benth leaves extracts. The hexane extracted Coleus aromaticus was added to the palm oil as the antioxidant agent. Then followed by several test such as peroxide value (PV), total acid number (TAN), iodine value (IV), and Fourier- Transform Infrared spectroscopy (FTIR) to study the oxidative stability of the palm oil after prolonged exposure to heat at 90 C for 0, 50, 100, 150, 200, 250, and 300 hours. The result of Coleus aromaticus Benth extract gave the positive effect in improving the oxidative stability of palm oil.